Foreign direct investment, domestic investment and economic growth in China: A time series analysis - Sumei Tang; E. A. Selvanathan; S. Selvanathan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
In this paper, we investigate the causal link between foreign direct investment (FDI), domestic investment and economic growth in China for the period 1988-2003. Towards this purpose, a multivariate VAR system with error correction model (ECM) and the innovation accounting (variance decomposition and impulse response function analysis) techniques are used. The results show that while there is a bi-directional causality between domestic investment and economic growth, there is only a single-directional causality from FDI to domestic investment and to economic growth. Rather than crowding out domestic investment, FDI is found to be complementary with domestic investment. Thus, FDI has not only assisted in overcoming shortage of capital, it has also stimulated economic growth through complementing domestic investment in China.
Keywords: C32; F21; O1; 330; foreign direct investment; domestic investment; economic growth; multivariate VAR system; error correction model; Direktinvestition; Investition; Wirtschaftswachstum; VAR-Modell; Fehlerkorrekturmodell; China